ANALISIS SEJARAH PERADABAN ISLAM TERHADAP TRADISI AL BARZANJI PADA MASYARAKAT MELAYU LABUHANBATU - Zulkifli Tanjung (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to explain the development of the history of Islamic culture in the Barzanji tradition and its relationship to the spread of Islam in the Labuhanbatu area. The Barzanji tradition has been practiced in Indonesia since the beginning of Islam. It is undeniable that the arrival of Islam has had a significant impact on culture. The same situation is observed in the tradition of reading barzanji in Labuhanbatu residents. This research method is a qualitative study using historical methods. Therefore, the following steps were taken during this study: methodological (data collection), verification (critical analysis of sources), interpretative and historiographical. In the data collection method, the author collected data from two sources: primary and secondary, after collecting data, analyzing and interpreting the results according to the sources and data obtained. Reading Barzanji in the community generally occurs at certain times, such as during the Hajj. However, the Barzanji tradition is not only carried out on this memorable day, but also on many other occasions as a commitment to achieve something greater, for example in the Labuhanbatu community when giving birth, aqiqah, circumcision, marriage, and other ceremonies.